Investigating Risk Factors for the Development of BK Virus Infection in Kidney Transplant Recipients in Guilan Province during 2007-2015 - Khosravi, Masoud; Dadras, Mahlagha; Monfared, Ali; Granmaieh, Siamak; Shenagari Rashti, Mohammad; Soltanipour, Soheil; Mokhtari, Gholamreza (Urology Journal, 2020)
Purpose: Polyomavirus nephropathy has been recognized as an important cause of silent loss of kidney transplant function in up to 50% of kidney recipients (1). The present study aimed to evaluate the risk factors associated with BK virus infection in kidney transplant recipients. Materials and Methods: Clinical information, urinary Decoy cells, and blood polymerase chain reaction (PCR) tests were collected for polyomavirus infection in 223 kidney transplant recipients undergoing surgery at Razi hospital at Guilan University of Medical Sciences between 2007 and 2015. Kidney biopsies were performed in patients with BKPyV- DNAemia more than 10,000 Copies/ml or increased plasma creatinine. Results: Among 223 patients, 116 (52%) were male. The mean age of participants was 49.57±13.48 years. Out of 223 participants, 41 (18.4%) had Decoy cells in their urine, and 182 (81.6%) did not, 15 of whom (6.7%) had viral genome in their blood. Only did 3 patients out of 10 have BK Virus nephropathy in their kidney biopsy. Among risk factors, it was found that post-transplant duration (P< 0.001) and the use of anti-thymocyte globulin (P= 0.001) were the most significant risk factors for finding decoy cells in patients’ urine. Conclusions: Post-transplant time, particularly the first 6 months, was found as the most important risk factor for the reactivation of polyomavirus infection in our patients because of strong immunosuppression and use of anti-thymocyte globulin (for prophylaxis or rejection treatment). It is concluded that kidney transplant recipients should be monitored in episodically after transplantation.